Behavioral and morphological contrasts on the reproduction of two prolonged breeders of the genus Physalaemus (Anura: Leptodactylidae) - Cajade, Rodrigo (2020)
Fil: Cajade, Rodrigo. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.